Nutritional Quality of Fruits and Vegetables 2014 - Vincente, Ariel R.; Manganaris, George A.; Ortiz, Cristian M.; Sozzi, Gabriel O.; Crisosto, Carlos H. (My University, 2014)
Chronic diseases such as heart disease, stroke, cancer and diabetes are a leading cause of mortality worldwide. Excess weight and outright obesity are a growing concern. Prevention of these problems is linked to lifestyle choices. There may be an evolutionary discordance between modern diets, rich in calories from fats and starches and low in fruits and vegetables, and human nutritional requirements. Consequently replacing some added sugars and saturated fat with more fruits and vegetables, may benefit health. A growing body of research indicates that fruit and vegetable consumption reduces the risk of major diseases and possibly delays the onset of age-related disorders. Traditional eating patterns of the Mediterranean region are associated with reduced cardiovascular disease. Although there is no single definition of a Mediterranean diet, descriptions emphasize the consumption of vegetables, fruits and nuts. In this chapter, we describe the main nutritional components and non-nutritional antioxidants present in fruits and vegetables, with special reference to the latest advancements. The influence of species, cultivar, maturity stage, postharvest storage conditions on these components is discussed.
Keywords: Fruit; Vegetables; Nutrition; Bioactive compounds; Antioxidants; Disease prevention